Identifikasi Jamur Penyebab Penyakit Pascapanen pada Beberapa Komoditas Bahan Pangan - PRATIWI, NOVA WAHYU; JULIANTARI, ERWINA; NAPSIYAH, LUTFI KHOTUN (Jurusan Biologi FMIPA Universitas Riau, 2016)
Food commodities can actually be stored for a long term after harvesting, but there are some constraintsof decrease in the quality of the fruit because of several postharvest diseases caused by microorganismssuch as fungi, bacteria, and viruses. The most frequently postharvest diseases trigger found is a group ofpathogenic fungi. The results of identification of fungi causing disease in several types of fruitpostharvest which were performed by blotter test method and medium PDA showed that Colletotricumcapsici fungi was found in chili, Rhizoctonia solani in bananas and tomatoes, Amerosporium sp. inpapaya, Pythium sp. on bananas, Fusarium solani on mango, banana, and papaya, and Phomopsis sp. ontomatoes.Keywords: fungi, food commodity, identification, postharvest diseases